THE EFFECTIVE TEACHING STRATEGIES TO ENCOURAGE YOUNG ADOLESCENT LEARNERS TO SPEAK ENGLISH - Eka Fajar Rahmani (IKIP PGRI Pontianak, 2017)
This qualitative study focuses on the discussion of effective teaching strategies to encourage young adolescent learners to speak English during the classroom activity. The purpose of this study is to present the speaking strategies used by young adolescent English teachers in Pontianak to motivate their students to speak English in their lesson. The participants involved five teachers in different level of education: elementary and lower secondary level, who were selected randomly to minimalize subjectivity to the research. The data were gathered by using open – ended interview. The results of the interview were described and narrated. The results showed that group work and drilling were frequently implemented by the teachers in their classroom to encourage their learners to speak. They confirmed that group work and drilling were appropriate to the level of English speaking skills of their learners.Keywords: speaking, group work, drilling.